Luxury consumption during hard times : Understanding the relationship between consumers’ emotional states and luxury consumption - Domi, Megi; Hudík, Marek, 1980-; Sharfaei, Shabab; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
The aim of this thesis is to analyse the relationship between weakened emotional states and the purchase of luxury products. The COVID-19 pandemic provides the ground for conducting such research. Literature that focuses on consumer behaviour in times of crisis argues that consumers in a pandemic situation buy luxury products to alleviate their feelings of fear and anxiety and have the tendency to increase their engagement with luxury. An empirical analysis of consumer behaviour during the pandemic on a sample of 108 respondents was conducted in order to test this hypothesis. It was found that emotional buying is at the center of pandemic luxury indulgence. This serves to suggest that appealing correctly to consumers’ emotional states would aid marketers and luxury brand managers in effectively conveying their communications strategies, attaining their profitability numbers, even in times of financial distress.
Vedoucí práce: Marek Hudík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses